2013 IEEE 24th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC) 2013
DOI: 10.1109/pimrc.2013.6666391
|View full text |Cite
|
Sign up to set email alerts
|

Block acknowledgment mechanisms for the optimization of channel use in wireless sensor networks

Abstract: One of the fundamental reasons for the IEEE 802.15.4 standard Medium Access Control (MAC) inefficiency is overhead. The current paper proposes and analyses the Sensor Block Acknowledgment MAC (SBACK-MAC) protocol, a new innovative protocol that allows the aggregation of several acknowledgment responses in one special BACK Response packet. Two different solutions are addressed. The first one considers the SBACK-MAC protocol in the presence of BACK Request (concatenation) while the second one considers the SBACK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…In Section III we provide an accurate analytical model for the throughput and end-to-end delay limits by considering our proposed BACK mechanism for both the cases of implementing or not BACK Request. Section IV provides both numerical and simulation results and extends our earlier work in [6] In our previous work in [6], we have shown that one of fundamental reasons for the IEEE 802.15.4 standard MAC inefficiency is overhead, and we have proposed a mathematical model that derives the throughput and end-to-end delay limits under ideal conditions (a channel environment without transmission errors). In the scope of our current research, we study the impact on the performance of the CSS and DSSS PHY layers and we also carry out a comparison against the IEEE 802.15.4 standard.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In Section III we provide an accurate analytical model for the throughput and end-to-end delay limits by considering our proposed BACK mechanism for both the cases of implementing or not BACK Request. Section IV provides both numerical and simulation results and extends our earlier work in [6] In our previous work in [6], we have shown that one of fundamental reasons for the IEEE 802.15.4 standard MAC inefficiency is overhead, and we have proposed a mathematical model that derives the throughput and end-to-end delay limits under ideal conditions (a channel environment without transmission errors). In the scope of our current research, we study the impact on the performance of the CSS and DSSS PHY layers and we also carry out a comparison against the IEEE 802.15.4 standard.…”
Section: Introductionmentioning
confidence: 64%
“…Like in [6], we analyse the maximum throughput, S max , and the minimum delay, D min , for the IEEE 802.15.4 DSSS and CSS PHY layers. S max is defined as the number of data bits generated from the MAC layer that can be transmitted per second to its destination including the ACK reception.…”
Section: Introductionmentioning
confidence: 99%
“…repetition of the backoff phase and IFS. Hence, although RTXs are an important source of overhead, the issue can be mitigated by using efficient RTX mechanisms. In [22], we have proposed a mathematical model that derives the throughput and end‐to‐end delay limits under ideal conditions (a channel environment with no transmission errors). In the scope of this research, we address both the best‐case scenario, where no transmission errors exist, and the more realistic case that considers transmission errors, which originates frame RTXs.…”
Section: Ieee 802154 In the Presence And Absence Of Rts/cts For Tmentioning
confidence: 99%
“…Consequently, the transmitter randomly selects a uniformly distributed backoff time period, in the range false[0,2BE1false]. It is worthwhile to mention that, even if there is only one transmitter and one receiver, the transmitter will always choose a random backoff period within false[0,2BE1false], which causes delay, as defined in [22]. Before starting a new transmission, each device sets initially the BE equal to macMinBE .…”
Section: Ieee 802154 In the Presence And Absence Of Rts/cts For Tmentioning
confidence: 99%
See 1 more Smart Citation